Phase 1/2 trial of glasdegib in patients with primary or secondary myelofibrosis previously treated with ruxolitinib. (April 2019) - Gerds, Aaron T.; Tauchi, Tetsuzo; Ritchie, Ellen; Deininger, Michael; Jamieson, Catriona; Mesa, Ruben; Heaney, Mark; Komatsu, Norio; Minami, Hironobu; Su, Yun; Shaik, Naveed; Zhang, Xiaoxi; et al.
Highlights: Glasdegib had an acceptable toxicity profile in patients with myelofibrosis. Most common adverse events were dysgeusia, muscle spasms, and alopecia. Modest improvements in patient-reported symptoms were observed with glasdegib. Spleen volume reduction (SVR) was noted in some patients, but no patient had ≥35% SVR. Abstract: Glasdegib is a potent and selective oral inhibitor of the Hedgehog pathway. We report data from the single-arm, lead-in cohort of an open-label phase 1b/2 trial of glasdegib in patients with primary/secondary myelofibrosis (MF) previously treated with at least one Janus kinase inhibitor (JAKi). Patients received glasdegib 100 mg orally once daily until there was no further clinical benefit. Primary endpoints included adverse events (AEs). Secondary endpoints included patients with spleen volume reduction (SVR) ≥35% at week 24, patients with ≥50% total symptom score (TSS) reduction, and pharmacokinetics. All 21 treated patients had one or more AE and five (23.8%) had serious AEs. Most common (>30%) AEs were dysgeusia (61.9%), muscle spasms (57.1%), alopecia (38.1%), fatigue (33.3%), and decreased appetite (33.3%). Although no patient had ≥35% SVR at week 24, one patient previously treated with ruxolitinib had an SVR of 32.9%. At week 12, two (9.5%) patients had ≥50% reduction in TSS from baseline and ˜40% had ≥20% reduction. One patient had an anaemia response. Following administration of glasdegib 100 mg once daily, the median time to peak plasma concentrations at steady-state generally occurred at 1 h post-dose. The safety profile of glasdegib monotherapy was manageable in patients with primary/secondary MF. Further study of glasdegib in combination with JAKi in a MF population may be warranted.